2020
DOI: 10.32529/beej.v1i2.1008
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Presentation, Practice, Production (Ppp) Method in Developing Students’ Speaking Skill at Ma Al-Khairaat Luwuk

Abstract: This research aims to find out the effectiveness of the Presentation, Practice, Production (PPP) method in developing students’ speaking skills at MA Al-khairaat luwuk. This research employed a pre-experimental research design involving one-group pre-test–post-test design. The independent variable of this research was Presentation, Practice, Production (PPP) method and the dependent variable was students’ speaking skills. The research population was eleventh-grade students of MA Al-khairaat Luwuk. There were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Widyantoro (2019) in the research which indicated that using the PPP method can make students engaged with the process of learning because they are provided opportunities to explore their potential by the teacher because when students can develop their potential; this can affect their speaking ability. These researches also in line with Sari & Sembiring (2019) andLakuana & Siojam (2020) which utilized the PPP method to enhance students' speaking skill in the classroom and got positive responses from students.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Widyantoro (2019) in the research which indicated that using the PPP method can make students engaged with the process of learning because they are provided opportunities to explore their potential by the teacher because when students can develop their potential; this can affect their speaking ability. These researches also in line with Sari & Sembiring (2019) andLakuana & Siojam (2020) which utilized the PPP method to enhance students' speaking skill in the classroom and got positive responses from students.…”
supporting
confidence: 60%
“…Another research from Lakuana and Siojam (2020) summarized that the PPP (Presentation, Practice, and Production) method had a substantial influence on increasing students' speaking skills. The research was pre-experimental research in senior high school.…”
Section: Theory Of Speakingmentioning
confidence: 99%
“…According to Thompson (2018), PPP can involve "explicit grammar instruction of target linguistic features which are then practiced using controlled activities before allowing the learner to use the form in free productive use" (p. 43). A recent study by Lakuana and Siojam (2020) found that applying the PPP method in English classrooms helped students effectively perform functions such as making suggestions and offers.…”
Section: Sequencing Conversation Strategy Instruction: the Three Psmentioning
confidence: 99%
“…The PPP method has received some criticism, especially by advocates of task-based language teaching and focus on form (e.g., Ellis, 2003;Long, 2016). However, some studies have shown positive results of PPP in teaching conversation strategies (e.g., Jones & Carter, 2014;Lakuana & Siojam, 2020). Jones and Carter (2014) found that learners considered the practice phase of PPP especially useful and that they performed better on the posttest than the non-PPP group, who received inductive instruction that did not use the practice phase.…”
Section: Sequencing Conversation Strategy Instruction: the Three Psmentioning
confidence: 99%